Status epilepticus in BRAF‐related cardio‐facio‐cutaneous syndrome: Focus on neuroimaging clues to physiopathology - Elisa Musto; Maria Luigia Gambardella; Marco Perulli; Michela Quintiliani; Chiara Veredice; Tommaso Verdolotti; Giovanna Berté; Chiara Leoni; Roberta Onesimo; Silvia Maria Pulitanò; Marco Tartaglia; Giuseppe Zampino; et al. (Epilepsia Open, 2024)
Abstract Objective Cardio‐facio‐cutaneous syndrome (CFC) is a genetic disorder due to variants affecting genes coding key proteins of the Ras/MAPK signaling pathway. Among the different features of CFC, neurological involvement, including cerebral malformations and epilepsy, represents a common and clinically relevant aspect. Status epilepticus (SE) is a recurrent feature, especially in a specific subgroup of CFC patients with developmental and epileptic encephalopathy (DEE) and history of severe pharmacoresistant epilepsy. Here we dissect the features of SE in CFC patients with a particular focus on longitudinal magnetic resonance imaging (MRI) findings to identify clinical‐radiological patterns and discuss the underlying physiopathology. Methods We retrospectively analyzed clinical, electroencephalogram (EEG), and MRI data collected in a single center from a cohort of 23 patients with CFC carrying pathogenic BRAF variants who experienced SE during a 5‐year period. Results Seven episodes of SE were documented in 5 CFC patients who underwent EEG and MRI at baseline. MRI was performed during SE/within 72 hours from SE termination in 5/7 events. Acute/early post‐ictal MRI findings showed heterogenous abnormalities: restricted diffusion in 2/7, focal area of pcASL perfusion change in 2/7, focal cortical T2/FLAIR hyperintensity in 2/7. Follow‐up images were available for 4/7 SE. No acute changes were detected in 2/7 (MRI performed 4 days after SE termination). Significance Acute focal neuroimaging changes concomitant with ictal EEG focus were present in 5/7 episodes, though with different findings. The heterogeneous patterns suggest different contributing factors, possibly including the presence of focal cortical malformations and autoinflammation. When cytotoxic edema is revealed by MRI, it can be followed by permanent structural damage, as already observed in other genetic conditions. A better understanding of the physiopathology will provide access to targeted treatments allowing to prevent long‐term adverse neurological outcome. Plain Language Summary Cardio‐facio‐cutaneous syndrome is a genetic disorder that often causes prolonged seizures known as status epilepticus. This study has a focus on electroclinical and neuroimaging patterns in patients with cardio‐facio‐cutaneous syndrome. During these status epilepticus episodes, we found different abnormal brain imaging patterns in patients, indicating various causes like brain malformations and inflammation. Understanding these patterns could help doctors find specific treatments, protecting cardio‐facio‐cutaneous syndrome patients from long‐term brain damage.